EFFECT OF TETRACYCLINE AND MALIC ACID ON THE PROTOLYTIC AND LIPOLYTIC BACTERIA IN COOLED STORED BEEF MEAT - Younis A. Y. Mashhadnay (Mesopotamia Journal of Agriculture)
The aim of this work was to study the effect of different concentration of tetracycline, malic acid and their mixture in different concentration in proteolytic and lipolytic bacteria count in the stored beef meat at 5oC. There was a gradual significant in proteolytic bacteria counts with the increase of storage time in all the treatments except in malic acid treatment where there was insignificant decrease in the number of these bacteria, in addition, there was a significant decrease in the treatments (30 ppm tetracycline and 1% malic acid and 30 ppm tetracycline and 1.5% malic acid) at the beginning of storage period, but with the continuation of storage, the number increased gradually till they reached a high number at the end of storage period and these increases in the bacteria counts in all the treatments were lesser than those in the control group during the storage. There was a decrease in Lipolytic bacteria counts in all treatment at the beginning of storage period except in control group and tetracycline treatments and the treatments (10 ppm tetracycline and 0.5% malic acid), but with the increase of storage period, the counts increased gradually and significantly in all treatments till they reach higher period, but they were lesser those in the control group.